THE RELATIONSHIP BETWEEN HEALTH FINANCING MECHANISM AND MORTALITY RATE IN SANTA MARIA PEKANBARU HOSPITAL - Arifin Arifin; Amal Chalik Sjaaf (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: The main challenge of the health financing mechanism in Indonesia is the allocation of health spending which is still dominated by the private sector, whereas the largest proportion comes from out of pocket payments. The system are a significant barrier in accessing health services. Many individuals with chronis diseases postpone the search for medical services because of high health care cost. The consequences of the delay is the loss of opportunities to overcome chronic illness. This research was aimed to analyze the relationship between health financing mechanism and mortality rate (GDR and NDR) in Santa Maria Pekanbaru Hospital. Methods: This cross-sectional study involves GDR and NDR of patients using out of pocket payment and those using health insurance in the year between 2014 - 2017. Data analysis was performed by independent samples t-Test (significance level p < 0,05). Result:The result of independent samples t-test analysis indicated that there was a significant difference between GDR and NDR of patients using out of pocket payment and health insurance patients (p < 0,05). GDR score of patients using out of pocket payment was 9.58 times higher than health insurance patients. The NDR score of patients with out of pocket payment 6.79 times higher than health insurance patients. Conclusion: The health service outcome in patients with out of pocket payment is lower than health insurance patients. The out of pocket payment financing mechanism is one of the major problems in the transition to Universal Health Covered. It is recommended that our government must increase the health budget which is at least in accordance with the rule of law and improve the allocation of public sector health funds at least 2/3 of the total health budget to reduce the proportion of out of pocket to total health expenditure. Health care providers should do efficiency in all areas to reduce the cost of health services. Patient who do not have health insurance will have to rearrenge the allocation of their household expense to pay premium insurance and implement the healthy life habits.